THE IMPLEMENTATION OF ENSEMBLE-BASED LEARNING IN ANGKLUNG AND BAMBOO MUSIC PROGRAM - Denhaz Nurul Hakim; Yupi Sundari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to implement and evaluate the effectiveness of an ensemble-based learning model in English language learning for vocational students majoring in Angklung and Bamboo Music. The research method used was classroom action research (CAR) conducted in two learning cycles. Data were collected through observation, reflection, and pretest–posttest to assess the development of students' language skills. The analysis showed an increase in average grades and student participation, although not very significant when calculated as a whole (average N-Gain <0.1). However, when only active students were counted, there was a more pronounced increase, with average attendance increasing from 67% to 70%. Qualitatively, students showed improvements in cooperation, self-confidence, and communication skills in a musical context. These findings indicate that ensemble-based learning is effective in increasing student engagement and motivation, especially for those who actively participate. This approach is relevant for vocational education because it is able to integrate elements of musicality with English communication in a contextual and creative manner. Keywords: ensemble-based learning, classroom action research, music vocational education, English for specific purpose